The Other Muslims
IX, 210 p.
Keywords: This book is a unique collection of alternative Muslim voices, predominantly from Europe, who come from a variety of backgrounds - academia, theology, acting, activism - and who make a transformational contribution to the debate of the future of Islam and Muslims in the West.